Japan and Malaysian development : (Routledge, 1994)
Japan and Malaysian Development critically assesses various dimensions of Japan-Malaysia economic relations. It discusses the impact and consequences of the controversial "Look East" policy. The contributors Jomo K. S. has gathered analyze the political dimension of that distinguished relationship. In particular, they examine issues such as trade relations, the different forms of Japanese direct investment, as well as the implications of joint ventures undertaken by both countries.In a highly balanced and unique manner, the contributors attend to concerns about labor and the cultural complexity involved in these transnational, capital ventures, providing a thorough understanding of this economic relation that has yet to have been examined elsewhere.